Preprocedural C-reactive protein predictive value in angiographic in-stent restenosis after coronary stent placement in patients with stable angina - Khosravi, AliReza; Kelishadi, Roya; Poormoghadas, Massoud; Shirani, Shahin; Asgary, Sedigheh; Khosravi, Mohammadreza (Archives of Medical Science, 2009)
Introduction: In spite of technological advances, restenosis after coronary stent implantation remains a long-term complication. Material and methods: Elective stent placement in a native coronary artery and 6-month angiographic follow-up were performed in 128 patients with stable angina. Coronary angiograms were reviewed by two cardiologists who were blinded to the blood test results. In-stent restenosis was defined as ł 50% reduction in diameter of the target lesion. Demographic variables and past medical history of patients as well as biochemical data including plasma level of CRP, fasting blood sugar and lipid profile were collected prospectively, and compared in patients with and without in-stent restenosis. Results: In-stent restenosis was observed in 46 patients (35.9%). The mean CRP concentration in restenotic and non-restenotic groups was 2.8 ±3.5 and 3.8 ±7.1 mg/l, respectively (p = 0.4) Restenosis rate in patients with high and low CRP concentrations were not statistically different (37.5 vs. 35%, respectively). The level of fasting blood sugar in restenotic patients was significantly higher than non-restenotic patients [102.3 ±39.7 vs. 84.5 ±28.9 mg/dl, OR 1.02 (1.00-1.04)]. Neither CRP level [OR 1.03, 95%CI (0.88-1.19)] nor other biochemical and clinical variables were associated with in-stent restenosis. Conclusions: Preprocedural CRP may not predict in-stent restenosis, but strict control of diabetes may improve the outcome after elective coronary stenting.